Science program behind Olympic golds. (Beijing Review, 1996)
Behind the great success of the Chinese athletes and coaches at the 26th Olympic Games was the Science and Education Program of the State Physical Culture and Sports Commission (SPCC). The remarkable progress made in a variety of sports events is due to scientific research into these sports. According to the deputy head of the Science and Technology Division under the Department of Science and Education of the SPCC, Lu Xiaojie, the domestic sports scientific research focuses on four areas: sports psychology, fatigue elimination, skill appraisal, and examination.